Exploring expectations and readiness for healthy lifestyle promotion in Swedish primary health care: a qualitative analysis of managers, facilitators, and professionals - Emma Nilsing Strid; Lars Wallin; Ylva Nilsagård (Taylor & Francis Group, 2024)
AbstractObjective Prior to a multifaceted implementation strategy for a healthy lifestyle-promoting practice the expectations of primary health care managers, appointed internal facilitators and health care professionals on supporting change was explored.Design This study had an explorative qualitative design using data gathered from individual interviews and focus groups. Qualitative content analysis with a deductive category development was applied using the Consolidated Framework for Implementation Research.Setting and participants The study was conducted in a primary care setting in central Sweden as a part of the Act in Time research project. Prior to a multifaceted implementation strategy, we held 16 individual interviews with managers and appointed facilitators and five focus groups with 26 health care professionals.Results Managers, facilitators, and professionals held similar expectations, where their expressed need for support corresponded to three constructs: Readiness for implementation, Implementation climate, and Engaging. Our findings indicate the need for strong leadership engagement to focus on how the healthy lifestyle-promoting practice can be anchored among the professionals. Managers at all levels should communicate the vision and goals, enable facilitators and professionals to improve their competencies, build inter-professional teams, and jointly plan the new practice.Conclusion To change to a healthy lifestyle promoting practice professionals request support from their managers, who in turn need support from the middle and top managers. The requested support includes helping to prioritise health promotion and enabling the primary care centres to build competence and take ownership of the implementation.Trial registration ClinicalTrials.gov NCT04799860